Beckwith Wiedemann Syndrome: A Case Report - Hassan, Md Kamrul; Paul, Amal Chandra; Shibli, Md Mizanur Rahaman (Faridpur Medical College Journal, 2016)
The baby with Beckwith Wiedemann Syndrome (BWS) usualy presents with exomphalos, macroglossia and gigantism. In addition, some children with BWS have other findings including: nevus flammeus, prominent occiput, midface hypoplasia, hemihypertrophy, genitourinary anomalies (enlarged kidneys), cardiac anomalies, musculoskeletal abnormalities, and hearing loss. Incidence of one in 13,700 live birth. As children with BWS are at increased risk of childhood cancer, they should follow up strictly for cancer screening. We are reporting this type of a case who has got Exomphalos, Macroglossia, Gigantism and Hemihypertrophy. We have corrected the exomphalos and advised him for follow up for cancer screening. Faridpur Med. Coll. J. Jul 2015;10(2): 87-88